Fasting serum fructose is associated with risk of gestational diabetes mellitus - Hongmei Zhang; Xiaoyong Li; Yixin Niu; Zhen Yang; Youli Lu; Qing Su; Li Qin (BMC, 2022)
Abstract Objective To investigate the association of fasting serum fructose concentrations and the incidence of GDM. Research design and methods Five hundred twenty six pregnant women who attended the obstetric clinic of Xinhua Hospital, Chongming Branch were recruited prospectively from September 2019 to November 2020. Fasting serum fructose concentrations were measured by a validated liquid chromatography-tandem mass spectrometry method. GDM was diagnosed according to the criteria of the IADPSG. Independent sample t-test was used to compare the differences between groups. Multiple stepwise regression analysis was used to estimate the associations of serum fructose and other variables. Multivariate logistic regression models were adopted to evaluate the odds ratios (ORs) for GDM. Results Of the 526 pregnant women, 110 were diagnosed with GDM. Fasting fructose concentrations were increased significantly in GDM patients compared to those without GDM (1.30 ug/ml vs 1.16 ug/ml, p<0.001). Fasting fructose concentration was independently associated with GDM after adjusting the potential confounders, 1 ug/ml increase in fasting serum fructose level was associated with an 81.1% increased risk of GDM (1.811, [1.155-2.840]). Taking fructose <1.036 ug/ml as the reference, the OR for GDM was significantly higher in fructose ≥1.036 ug/ml group (OR, 1.669; 95% CI, 1.031-2.701) after all the potential confounders were adjusted. Conclusions Increased fasting serum fructose levels were independently associated with the incidence of GDM.